2023
DOI: 10.3389/fneur.2023.1069411
|View full text |Cite
|
Sign up to set email alerts
|

Plasma biomarkers for diagnosis of Alzheimer's disease and prediction of cognitive decline in individuals with mild cognitive impairment

Abstract: BackgroundThe last few years have seen major advances in blood biomarkers for Alzheimer's Disease (AD) with the development of ultrasensitive immunoassays, promising to transform how we diagnose, prognose, and track progression of neurodegenerative dementias.MethodsWe evaluated a panel of four novel ultrasensitive electrochemiluminescence (ECL) immunoassays against presumed CNS derived proteins of interest in AD in plasma [phosphorylated-Tau181 (pTau181), total Tau (tTau), neurofilament light (NfL), and glial … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Studies that have been composed of persons with mild cognitive impairment (MCI), dementia, or combinations of impaired and CU individuals have shown the ability of plasma biomarkers to predict cognitive outcomes including, in some studies, person‐level prediction. 3 , 17 , 40 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 We recognize that biomarkers should have greater power to predict decline rates among individuals who are impaired at baseline and who are exhibiting more uniform cognitive decline in comparison to CU individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Studies that have been composed of persons with mild cognitive impairment (MCI), dementia, or combinations of impaired and CU individuals have shown the ability of plasma biomarkers to predict cognitive outcomes including, in some studies, person‐level prediction. 3 , 17 , 40 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 We recognize that biomarkers should have greater power to predict decline rates among individuals who are impaired at baseline and who are exhibiting more uniform cognitive decline in comparison to CU individuals.…”
Section: Discussionmentioning
confidence: 99%
“… 8 , 9 , 38 , 42 , 43 , 44 , 45 , 46 As such, our broad results are in keeping with the idea that GFAP and NfL are not specific to a single neurodegenerative disease process, and support some neuropathological overlap across these diseases, especially in AD/MCI and PD. Other studies have also investigated the association of GFAP and NfL with cognition, albeit predominantly with screening tools of global cognition (e.g., Mini‐Mental State Examination [MMSE], MoCA), and have found elevated GFAP to be associated with worse baseline cognition or cognitive decline in AD/MCI, 10 , 47 PD or other synucleinopathies, 38 or FTD, 37 , 48 while others did not. 10 , 49 Similarly, studies have found elevated NfL to be associated with worse cognition or cognitive decline in AD/MCI, 8 , 10 , 42 , 50 PD or other synucleinopathies, 44 , 45 , 46 , 50 , 51 , 52 , 53 or FTD, 54 while others did not.…”
Section: Discussionmentioning
confidence: 99%
“… 10 , 49 Similarly, studies have found elevated NfL to be associated with worse cognition or cognitive decline in AD/MCI, 8 , 10 , 42 , 50 PD or other synucleinopathies, 44 , 45 , 46 , 50 , 51 , 52 , 53 or FTD, 54 while others did not. 10 , 47 , 48 , 49 , 53 , 55 …”
Section: Discussionmentioning
confidence: 99%
“…GFAP levels have recently been reported to be predictive of conversion of MCI to AD-dementia in several studies with steeper trends of conversion for cognitively abnormal groups ( 99 , 100 ) and were able to discriminate between MCI individuals who progressed to dementia and non-progressors ( 101 ). GFAP serum levels were also found to detect AD pathology in patients with MCI ( 99 ).…”
Section: Brain-immune System Crosstalk In Alzheimer’s Diseasementioning
confidence: 99%